Lived Experiences of Resilient Overseas Filipino Workers in Their Career Journey: Towards the Development of Thematic Intervention Module - Corazon A. De Jesus; Lorvin M. Adducul (Studies in Social Science & Humanities, 2024)
The life journey of Overseas Filipino Workers (OFWs) is a testament to resilience and sacrifice, as they navigate grueling work conditions, cultural barriers, and prolonged separation from their families, all in pursuit of better opportunities and a brighter future for their loved ones. This study, using a descriptive qualitative research method with personal interviews, was conducted to explore the lived experiences of OFWs concerning work challenges, employment conditions, cultural adaptation, social integration, family impact, personal well-being, coping mechanisms, and prospective initiatives. Findings show that OFWs face demanding work schedules, language barriers, job insecurity, and discrimination, leading to physical and mental stress. Cultural adaptation is crucial but challenging, often causing emotional distance and communication breakdowns with family. Coping mechanisms include regular family communication, community engagement, and support from fellow expatriates. Improving OFWs’ experiences requires targeted policies and programs. Moreover, challenges for OFWs in Kuwait include long working hours, physical exhaustion, job insecurity, low pay, language barriers, cultural differences, and discrimination. These challenges impact their well-being, financial stability, and job satisfaction. Addressing these issues requires supportive workplace policies, fair treatment, job security, and reasonable working hours. Consequently, this study proposes an intervention program that supports OFWs from pre-departure to their return to the Philippines, covering support systems, financial empowerment, and career development. It is essential for the Philippine Government, NGOs, and host countries to establish favorable conditions to support OFWs throughout their employment abroad, regardless of their duration of stay.